Anti‐Helicobacter pylori therapy in localized gastric mucosa‐associated lymphoid tissue lymphoma: A prospective, nationwide, multicenter study in Japan. Issue 2 (4th March 2018) - Sugizaki, Katsuya; Tari, Akira; Kitadai, Yasuhiko; Oda, Ichiro; Nakamura, Shotaro; Yoshino, Tadashi; Sugiyama, Toshiro
Abstract: Background: Helicobacter pylori eradication therapy was approved in Japan for the first‐line, standard treatment of H. pylori ‐positive gastric mucosa‐associated lymphoid tissue (MALT) lymphoma. Although several retrospective studies or small‐scale single‐center studies have been reported, a prospective, large‐scale, nationwide, multicenter study has not been reported from Japan. Materials and Methods: We conducted a prospective, nationwide, multicenter study to evaluate the clinical efficacy of rabeprazole‐based triple H. pylori eradication therapy for patients with localized gastric MALT lymphoma in practice‐based clinical trial. A total of 108 H. pylori ‐positive patients with stage I/II1 gastric MALT lymphoma underwent H. pylori eradication therapy. The primary endpoints were complete remission (CR) rate and the rate of transfer to secondary treatment. The secondary endpoints were CR maintenance duration and overall survival (OS). Results: CR of lymphoma was achieved in 84 of 97 patients (86.6%), during the period 2.0‐44.7 months (median, 5.3 months) after starting H. pylori eradication treatment. CR was maintained in 77 of 81 patients (95.1%) for 0.4‐53.2 months (median, 33.1 months). Secondary treatments (radiotherapy, rituximab, or gastrectomy) for gastric MALT lymphoma were needed in 10 of the 97 patients (10.31%). During follow‐up, OS rate was 96.9% (94/97) and the causes of 3 deaths were not related to lymphoma. Conclusions: Rabeprazole‐based H. pylori eradication therapy demonstrated a high CR rate, long CR maintenance, and a good OS for patients with localized gastric MALT lymphoma in this prospective, practice‐based, multicenter study.